Evidence-Based Design Principles for Spanish Pronunciation Teaching - Colantoni, Laura; Escudero, Paola; Marrero-Aguiar, Victoria; Steele, Jeffrey (Frontiers in Communication, 2021)
In spite of the considerable body of pedagogical and experimental research providing clear insights into best practices for pronunciation instruction, there exists relatively little implementation of such practices in pedagogical materials including textbooks. This is particularly true for target languages other than English. With the goal of assisting instructors wishing to build effective evidence-based instructional practices, we outline a set of key principles relevant to pronunciation teaching in general, illustrated here via Spanish in particular, drawing on previous pedagogical research as well as methods and findings from experimental (applied) linguistics. With the overall goal of enabling learners to move towards greater intelligibility, these principles include the importance of perceptual training from the onset of learning, a strong prosodic component, the use of contextualized activities, and a focus on segmental and prosodic phenomena with a high functional load as well as those that are shared across target language varieties. These principles are then illustrated with innovative perception and production exercises for beginner, university-level learners of Spanish. We conclude with a discussion of ways in which the pedagogical principles exposed here can be extended beyond the production of individual activities to the design of a broader pronunciation curriculum.